Thermally stable deep-red emitting Sr2GdTaO6:Mn4+ double perovskites for indoor plant growth LEDs. (March 2022) - Han, B.; Yang, X.; Ren, J.; Liu, L.; Zhao, E.; Zhu, X.; Zhu, J.; Ma, H.; Li, A.; Teng, P.
Abstract: Indoor artificial cultivation of plants is a novel technology applied to agriculture, and the emission band of luminescent materials can be matched with the needs of plants to promote plant growth. In this contribution, novel Mn 4+ doped Sr2 GdTaO6 (SGTO) deep-red phosphor was synthesized. This material was characterized, in detail, by X-ray diffractometer, SEM, and photoluminescence emission spectra. Sr2 GdTaO6 :Mn 4+ (SGTO:Mn 4+ ) can be effectively excited by near-ultraviolet (NUV) light, and the broadband emission of deep-red light matches the absorption band of plant phytochromes PR and PFR . The optimum doping concentration of Mn 4+ in SGTO was 0.6 mol%, and the concentration quenching mechanism was attributed to dipole-quadrupole ( d - q ) electric interaction. The photoluminescence emission intensity of SGTO:0.006Mn 4+ at 423 K is 80.6% of that at room temperature and the internal quantum efficiency of SGTO:0.006Mn 4+ is 36.09%. Finally, the performance of the commercial 440 nm light-emitting diode chip/SGTO:0.006Mn 4+ encapsulated light-emitting diode device was stable and can meet the needs of plants for the blue and red light. The results showed that SGTO:0.006Mn 4+ deep-red phosphor is expected to be a phosphor suitable for indoor plant growth lighting. Highlights: Novel Mn 4+ -doped Sr2 GdTaO6 deep-red phosphor was synthesized. The photoluminescence emission intensity of Sr2GdTaO6 :0.006Mn 4+ at 423 K is 80.6% of that at room temperature. The light-emitting diode device has potential application value in the field of plant lighting.